Colloquium on the Eastern Policy of the Capitalist Countries (Czech Journal of International Relations, 1967)
"In the last decade, issues of relations between socialist and capitalist states have become a key factor in world politics and a barometer of the international atmosphere. You then find yourself in Europe, where the two systems are directly adjacent and where the situation is complicated by a number of open questions. The development of the tension between the East and the West in the current period — in connection with the overall world trend and its reflection of the unity of both groups particularly accelerated and presents new political theory and practice of both parties to foreign countries tasks ...*